Motor control model of a swing on gymnastic rings - Imai, S.; Yamasaki, T.; Yamawaki, K.; Xin, X.; Izumi, S. (The Proceedings of the Symposium on sports and human dynamics 2017, 2017)
We examined whether a swing on gymnastic rings can be performed by control for achieving an inter-joint coordination. The swing in the sagittal plane was modeled by a three-segment model with two degrees of underactuation. The coordination was modeled by a linear relation among joint angles as a virtual holonomic constraint. The controller was constructed by the partial feedback linearization. The simulation results showed that the model had solutions similar to steady swings in gymnastics, and the swing amplitude can be increased by switching two inter-joint coordination.